Antimicrobial resistance in the practice of primary care physicians: an introduction to the problem - Hanna Laudy-Wiaderny; Aneta Nitsch-Osuch (Family Medicine & Primary Care Review)
Antimicrobial resistance (AMR) is a vital healthcare crisis with profound implications. On a global scale, the efficacy of antibiotics is compromised by AMR, rendering previously reliable treatments ineffective. This poses a significant concern for modern medicine, as routine medical procedures and common infections could become life-threatening. Projections state that by 2050, more individuals globally could die from drug-resistant infections than from cancer if AMR is not addressed. Concern about AMR in Poland reflects the global issue. The misuse and overuse of antibiotics in health care, agriculture, and daily life have contributed to the development of drug-resistant bacterial strains. Treating common infections is becoming more complex, and as a result, the economic burden on the healthcare system increases. To combat AMR in Poland, initiatives to raise awareness, promote responsible antibiotic use, enhance surveillance, and improve infection control and prevention practices are underway. AMR raises a complex challenge that requires intersectoral collaboration across health care, agriculture, and policymaking. Failure to comprehensively address this puts the future of health care at risk, emphasizing the urgent need for global and local action. This article, the first in a series on AMR and rational antibiotic use in primary care facilities, aims to introduce the reader to this complex issue.